STANDARISASI BAHASA - I Wayan Mawa (WACANA : MAJALAH ILMIAH TENTANG BAHASA, SASTRA DAN PEMBELAJARANNYA, 2022)
The use of language much morre depend on, when, who use it. This happens because of the dynamic characters of language. It means that languange will always develope in accordance with the development and dynamics of sociaty. Whether the language changes quickly or not it depends on intrinsic and extrinsic factors. Intrinsic factors consist of character of language itself namely, established, fleksible or adapted. Beside that the important thing in dynamics as of language is that how important the rule of the language as the referance of the other dialecs. Apart from the intrinsic factors. The extrimsics factors also have important rule in the dymamics of development of language. This concerning wheter. The language itself fungtion as a mean of unity or as the identity of the speakers. Key words: Language, Standardisation